Motivasi Petani Menanam Padi Varietas Lokal (Siam) di Kecamatan Pandawan Kabupaten Hulu Sungai Tengah - Ristiani Ristiani; Nina Budiwati; Usamah Hanafie (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
Agricultural sector has important role in economic development of Kabupaten Hulu Sungai Tengah. This area is food basket for the province as well as the buffer of national food security. Around 70% of people rely on agricultural sector, including subsector of crop, horticulture, plantation, husbandry, and fishery . The study is purposed : (1) to understand the farmer motivation in growing local variety; (2) to analyze the correlation between selected factors d (ie.: seed availability , last year rice productivity, and rice price) and farmer motivation to cultivate local variety; and (3) to identify the obstacles of local variety cultivation, The farmers motivation in growing local variety is categorized as medium (score 79.37%). This motivation is also not correlated to the seed availability, last year rice productivity, and rice price. Meanwhile, the brown planthopper outbreak is the biggest challenge. The pest causes dried leaves and stem, which lead to the harvest loss.